VALUASI EKONOMI DENGAN TRAVEL COST METHOD PADA OBYEK EKOWISATA PULAU-PULAU KECIL (Kasus Kawatan Kepulauan Seribu) - M. Yuwana Marjuka (Bina Ekonomi, 2007)
The phenomenal growth of global tourism has immediate and far reaching consequences for the natural and cultural heritage, as it directly links tourism activities with low impact use of the natural resources, environmental conservation and sustainable economic activities. One among many terms given to this form of tourism is ecotourism sectors. The rapidly growing ecotourism movement for coastal zone of tourism attraction, in this case Just like the ecotourism in the Kepulauan Seribu, Jakarta Utara area natural green sea turtle conservation, coral reef and sandy coastal scenery, fishing community, and others various natural . Potentials can be beneficial to attract domestic tourists as well as international tourists. The travel cost method can use to estimate economic use values associated with ecosystems or sites that are used for recreation such Kepulauan Seribu Area. The method can be used to estimate the economic benefits or costs resulting from: 1) changes in access costs for a recreational site, 2) elimination of an existing recreational site, 3) addition of a new recreational site, and 4) changes in environmental quality at a recreational site. The basic premise of the travel cost method is that the time and travel cost expenses that people incur to visit a site represent the "price" of access to the site. Thus, peoples' willingness to pay to visit the site can be estimated based on the number of trips that they make at different travel costs. This is analogous to estimating peoples' willingness to pay for a marketed good based on the quantity demanded at different prices. This section continues with example applications of the travel cost method to analyze the ecotourism in the Kepulauan Seribu area, followed by a more complete technical description of the method and its advantages and limitations.